A Peculiar Case of Ossicular Chain Fixation and Enlarged Vestibular Aqueduct - Davide Brotto; Marzia Ariano (Children, 2023)
We present the case of a patient treated as affected by conductive hearing loss due to recurrent otitis, then as a juvenile otosclerosis, who was finally diagnosed as affected by bilateral ossicular chain fixation and enlarged vestibular aqueduct by means of cone-beam CT.